PELAKSANAAN BAURAN PROMOSI PADA HARRIS RESORT WATERFRONT BATAM - M. Nazarudin Syah; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The influence of Covid-19 has greatly impacted the world of hospitality, many hotels in Indonesia are currently experiencing a slump. Harris Resort Waterfront Batam is one of the four-star resorts that still survives in the city of Batam with the implementation of an effective promotion mix to increase occupancy. Harris Resort Waterfront is still in a stable condition. Promotional mix is the best combination of strategies from promotional elements carried out by a company, it is necessary to determine in advance what equipment or promotional elements should be used and how to coordinate these elements so that the results can be optimal. Therefore, this study aims to determine the implementation of the promotion mix at Harris Resort Waterfront Batam. This study uses a qualitative descriptive method to analyze problems based on data collection techniques in the form of observation, in-depth interviews, and documentation. Promotion Mix includes reporting on conditions carried out in advertising, sales promotion, public relations, personal selling and direct marketing. Based on the results of the research that has been carried out, for the overall results of observations and interviews, it can be concluded that the implementation of the Harris Resort Waterfront Batam Promotion Mix has not fully worked out as targeted. Keywords: Hotel, Promotionl Mix, Harris Resort Waterfront Batam